Role Models of The Early Christians’ Life (Acts 2:41-47) for Pastoral Lingkungan in The Archdiocese of Semarang - Aditya - Relliantoko; Feremenatos Oktafilio Adi Prasetya; Antonius Galih Arga Wiwin Aryanto (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2024)
In the context of pastoral care, the Church of the Archdiocese of Semarang has created a policy of establishing small base groups among the community. Each parish in the Semarang Archdiocese is subdivided into sub-groups, which are then referred to as kring or lingkungan. The existence of ‘lingkungan’ certainly cannot be separated from the pastoral initiative of the missionaries at the beginning of the mission Church in Java Island. The missionaries, who were very limited in terms of numbers and services, were greatly helped by the presence of Catholic teachers who were present in remote villages and involved in preaching the Gospel for the community. In this study, the authors attempt to see the relevance of the life of the local Church community and the ideal of the Early Church as depicted in Acts 2:41-47. The situation of the early community lived in a basic group that was diligent in prayer and togetherness, was seen as an ideal model to be achieved through Church life in an based group of ‘lingkungan’.